Action Research Restoration Trials Borana Zone and Somali Region, Ethiopia - Sircely, Jason; Eba, Bedasa; Nganga, Irene; Flintan, Fiona E. (International Livestock Research Institute, 2024)
A report of action research restoration trials undertaken in Ethiopia with support of the HEAL (Humans Environment, Animals and Livelihoods) project and the CGIAR Initiative on Livestock and Climate.